Pedagogy and Andragogy: project-based education to promote active and meaningful learning - Sousa, Rodger Roberto Alves de (Revista Interseção, 2024)
ABSTRACT Project-based education is a pedagogical and andragogic approach that seeks to actively engage students in meaningful projects. This study presented a review of the concepts and characteristics of pedagogy and andragogy, highlighting their similarities and differences. In addition, it explored the benefits of this approach, such as the development of cognitive, social-emotional and practical skills, as well as student motivation and engagement. The principles of active and meaningful learning were discussed, emphasizing the importance of contextualization, relevance and practical application of knowledge. The structure and stages of project-based education were explained, emphasizing goal setting, task organization, role division, and project evaluation. The role of the educator as a facilitator and advisor in this context was analyzed, highlighting his role in promoting autonomy, teamwork and critical thinking of students. Practical examples of educational projects based on pedagogy and andragogy were presented, addressing different age groups and areas of knowledge. The challenges of implementing this approach have been identified, along with strategies to overcome them. Finally, we discussed the observed results, including learning, developed skills and student engagement, and the impact of this approach on the integral formation of individuals. This review highlights the importance of project-based education as a way to promote active and meaningful learning, contributing to the development of autonomous, critical and prepared students for the challenges of the twenty-first century. Keywords: Project-Based Education. Active Learning. Meaningful Learning. Pedagogy. Andragogy. RESUMO A educação baseada em projetos é uma abordagem pedagógica e andragógica que busca envolver os alunos de forma ativa em projetos significativos. Este estudo apresentou uma revisão dos conceitos e características da pedagogia e andragogia, destacando suas semelhanças e diferenças. Além disso, explorou os benefícios dessa abordagem, como o desenvolvimento de habilidades cognitivas, socioemocionais e práticas, bem como a motivação e engajamento dos alunos. Os princípios da aprendizagem ativa e significativa foram discutidos, ressaltando a importância da contextualização, relevância e aplicação prática do conhecimento. A estrutura e etapas da educação baseada em projetos foram explicadas, enfatizando a definição de objetivos, organização das tarefas, divisão de papéis e avaliação do projeto. O papel do educador como facilitador e orientador nesse contexto foi analisado, destacando sua função em promover a autonomia, trabalho em equipe e pensamento crítico dos alunos. Exemplos práticos de projetos educacionais baseados em pedagogia e andragogia foram apresentados, abordando diferentes faixas etárias e áreas do conhecimento. Os desafios da implementação dessa abordagem foram identificados, juntamente com estratégias para superá-los. Por fim, discutiu-se os resultados observados, incluindo aprendizagem, habilidades desenvolvidas e engajamento dos alunos, e o impacto dessa abordagem na formação integral dos indivíduos. Essa revisão ressalta a importância da educação baseada em projetos como uma forma de promover uma aprendizagem ativa e significativa, contribuindo para o desenvolvimento de alunos autônomos, críticos e preparados para os desafios do século XXI. Palavras-chave: Educação Baseada em Projetos. Aprendizagem Ativa. Aprendizagem Significativa. Pedagogia. Andragogia.